A user-centred approach to requirements elicitation in medical device development: a case study from an industry perspective - Martin, Jennifer. L.; Clarke, Daniel J; Morgan, Stephen P; Crowe, John A; Murphy, Elizabeth (Elsevier, 2012)
The healthcare industry is dependent upon the provision of well designed medical devices. To achieve this it is recommended that user-centred design should begin early, and continue throughout device development. This is a challenge, particularly for smaller companies who may lack the necessary expertise and knowledge. The aim of this study was to conduct a rigorous yet focused investigation into the user requirements for a new medical imaging device. Open-ended semi-structured interviews were conducted with potential clinical users of the device to investigate the clinical need for the device and the potential benefits for patients and clinical users. The study identified a number of new and significant clinical needs that suggested that the concept of the device should be fundamentally changed. The clinical and organisational priorities of the clinical users were identified, as well as a number of factors that would act as barriers to the safe and effective adoption of the device. The developers reported that this focused approach to early requirements elicitation would result in an improved product, reduce the time to market, and save the time and cost of producing and evaluating an inappropriate prototype.